Detection of SHV and TEM-type Extended spectrum Î²-lactamase in bacterial isolates recovered from clinical samples of patients attending military hospitals - Ogefere, Helen Oroboghae; Iriah, Samuel E.; Ibadin, Ephraim Ehidiamen (Faculty of Medicine, Trisakti University, 2019)
BackgroundMulti-drug resistant bacterial strains have been increasingly implicated in clinical infections worldwide and beta-lactamase production is one of the commonest mechanisms of resistance in these strains. This study investigated the prevalence of extended spectrum Ã¢-lactamase (ESBL)-producing isolates and determined the temoneira (TEM) and sulfhydryl variable (SHV) types implicated in two military hospitals in South-South Nigeria. MethodsThree-hundred and eighty (380) consecutive non-duplicate bacterial isolates (Gram negative bacilli) recovered from clinical samples were identified following standard techniques. Antimicrobial susceptibility tests were performed for each isolate following the Clinical Laboratory Standards Institute guidelines. Bacterial isolates recovered which comprised Escherichia coli, Klebsiella spp, Proteus spp and Pseudomonas aeruginosa were screened for ESBL using a phenotypic method (double disc synergy test). All positive isolates were screened for TEM and SHV genes by PCR method. ResultsSixty-five isolates (17.1%) were ESBL producing using phenotypic method, E. coli showed the highest ESBL prevalence (24.3%). One isolate was SHV positive (1.5%), 8 (12.3%) were TEM positive while 3 (4.6%) isolates harbored both SHV and TEM genes. Fluoroquinolone - ofloxacin showed marked activity against ESBL-producing isolates (90.8%) while the least active were ceftriaxone (9.2%), ceftazidime (3.1%) and ampicillin (1.5%). ConclusionThis study demonstrated that 17.1% of Gram-negative bacilli were ESBL producers. Screening of clinical isolates for ESBL should be implemented. The findings of this study suggest the need for caution in the use of antimicrobial agents in order to curb the incidence of antimicrobial resistance.